2018
DOI: 10.1007/s00380-018-1149-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac unloading by LVAD support differentially influences components of the cGMP–PKG signaling pathway in ischemic and dilated cardiomyopathy

Abstract: Implantation of left ventricular assist devices (LVADs) as bridge to transplant in end-stage heart failure allows for analyzing reverse remodeling processes of the supported heart. Whether this therapy influences the cGMP-PKG signaling pathway, which is currently under thorough investigation for developing new heart failure therapeutics, is unknown. In fourteen end-stage heart failure patients (8 with dilated cardiomyopathy, DCM; 6 with ischemic cardiomyopathy, ICM) tissue specimens of left ventricles were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Previous studies have indicated that aberrant JAK/STAT signaling may promote progression from hypertrophy to HF (43)(44)(45). In addition, the cGMP/PKG signaling pathway, adrenergic signaling in cardiomyocytes, and the p53 signaling pathway are also reportedly involved in the pathogenesis of HF (46)(47)(48)(49)(50)(51)(52). The enrichment findings of the present study are in line with the aforementioned conclusions, further strengthening the reliability of the present results.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have indicated that aberrant JAK/STAT signaling may promote progression from hypertrophy to HF (43)(44)(45). In addition, the cGMP/PKG signaling pathway, adrenergic signaling in cardiomyocytes, and the p53 signaling pathway are also reportedly involved in the pathogenesis of HF (46)(47)(48)(49)(50)(51)(52). The enrichment findings of the present study are in line with the aforementioned conclusions, further strengthening the reliability of the present results.…”
Section: Discussionsupporting
confidence: 91%
“…The Calcium signaling pathway can increase calcium load and cause cardiovascular diseases such as arrhythmia [49]. The cGMP-PKG signaling pathway regulates vascular circulation and induces arterial relaxation [50].The cAMP signaling pathway is one of the signals activate G-protein in intracellular information transmission and activator by binding to specific receptors on the cell membrane, and then promote the transformation of adenosine triphosphate into cAMP [51]. The PI3K-Akt signaling pathway promotes the expression of PI3K, Akt proteins and activates thrombopoietin receptor-2, thus promoting neovascularization [52].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic guanosine monophosphate (cGMP) is a cyclic nucleotide derived from GTP (guanosine triphosphate) that acts as a second messenger for activation of intracellular protein kinases in response to the binding of membrane-impermeable hormones to the cell membrane [126]. The important components of cGMP signaling include cGMP-dependent protein kinase G (PKG), ANP, BNP, natriuretic peptide receptor A and C (NPR-A and NPR-C, respectively), neprilysin, NOS3, soluble guanylyl cyclase (sGC), and PDE5 [127]. The cGMP-PKG cascade can decrease the level of calcium and alter the expression of glycoprotein IIb/IIIa.…”
Section: Cyclic Guanosine Monophosphatementioning
confidence: 99%